2017
DOI: 10.4018/978-1-5225-2101-3.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storytelling and Digital Literacy

Abstract: This chapter reveals the overview of digital technologies; the overview of digital storytelling in education; and the overview of digital literacy in education. Digital storytelling and digital literacy are very important in modern education. Digital storytelling is used to improve student's learning through multimedia in the modern classrooms. Digital storytelling is the expressive medium that can explain even the most intricate topics in depth, integrating it with the rest of the curriculum. Digital literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…The results from the digital storyboarding content in the current study showed that cohesion was maintained or at least attempted across sentence structures and word correlativity, as shown in Table 11. While digital storytelling is still recent compared to other e-learning techniques to be integrated into education or language learning to be specific, it can improve problemsolving, creativity, perspective building, and higher-order thinking [49].…”
Section: Digital Storyboardingmentioning
confidence: 99%
“…The results from the digital storyboarding content in the current study showed that cohesion was maintained or at least attempted across sentence structures and word correlativity, as shown in Table 11. While digital storytelling is still recent compared to other e-learning techniques to be integrated into education or language learning to be specific, it can improve problemsolving, creativity, perspective building, and higher-order thinking [49].…”
Section: Digital Storyboardingmentioning
confidence: 99%